2019
DOI: 10.5121/ijcnc.2019.11202
|View full text |Cite
|
Sign up to set email alerts
|

Design of Secure and Reliable MU-MIMO Transceiver System for Vehicular Networks

Abstract: MU-MIMO (Multi-User MIMO) has been a promising technique for vehicular networks to achieve faster communication. Conventional MU-MIMO transceiver is designed with One-dimensional (1-D) improper modulation schemes such as Binary Phase Shift Keying (BPSK) and Multilevel Amplitude Shift Keying (M-ASK) failed to yield standard ABER (average bit error rate). To achieve high reliability, a novel MU-MIMO uplink transceiver system is designed under PAPC (Per-Antenna Power Constraint) by assuming perfect and imperfect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It is observed that the proposed LFSR based key generation technique has a larger key size when compared to the existing technique ( [32,33]). Although the key size in [34] is larger, the strength of the algorithm is moderate indicated by its lower-key generation time when compared to the proposed technique. The key space is used to determine the strength of the generated key over brute force attacks.…”
Section: Complexity Level Estimationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is observed that the proposed LFSR based key generation technique has a larger key size when compared to the existing technique ( [32,33]). Although the key size in [34] is larger, the strength of the algorithm is moderate indicated by its lower-key generation time when compared to the proposed technique. The key space is used to determine the strength of the generated key over brute force attacks.…”
Section: Complexity Level Estimationmentioning
confidence: 99%
“…Moreover, the performance of the proposed security algorithm is compared with the existing techniques [32][33][34]. All these techniques are applied to a single random image to make uniform test conditions.…”
Section: Complexity Level Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested to consider the use of either smart or multiple antenna technology to improve performance. Moreover, because of the Alamouti's scheme MIMO antenna technology is very similar to smart antenna technology and is one of the most efficient leading innovations in wireless systems for maximum capacity, improved QoS and coverage extension range [52,53,74]. The effect of MIMO antennas on near-space solar-powered platforms performance and capacity is discussed in [54][55][56], where it is argued that the antenna gain has to be optimized, otherwise, user ends will experience weak radio across a distance of many miles.…”
Section: Wireless Communications: Aerial Systemsmentioning
confidence: 99%